Intervention Strategies for Equity in Education: Synchronised and Co-ordinated Model to Help Learners Cope with Absence of Parents Due to Migration in Zimbabwe - Winniefridah Matsa (Springer, Cham, 2023)
Western ideas, concepts and definitions have influenced and continue to influence the educational policies and practices of former colonies. The imported western educational policies universalise and homogenise western and non-western countries, assuming that everyone has social and economic capital thereby ignoring issues of cultural deprivation, marginalisation impinging on equity in education. The chapter is premised on the debates of western intervention equity policies in education versus post-colonial ones. The chapter begins with the historical context of western intervention equity policies in education and their impact in Zimbabwe. Post-colonial theoretical lenses lay the foundation of transformatory, migratory and education policies as well as strategies suggested in this book for migrants’ children to cope with absence of parents due to migration. Transformatory policies and strategies acknowledge diversity and unequal distribution of resources. The current strategies borrow from western equity policies ignore diversity and different political, economic and cultural contexts. The strategies are fragmented, adaptive and not transformatory. The model suggests synchronised and coordinated transformatory strategies.